The spirit within me: self and agency in ancient Israel and Second Temple Judaism - Newsom, Carol Ann (The Anchor Yale Bible reference library, 2021)
The self in Israelite culture: a preliminary overview -- Agency in Biblical narrative -- Moral agency in Israelite perspective: three case studies -- Sin-consciousness, self-alienation, and the construction of interiority -- Rational agency and the birth of the human: Genesis 2-3 and its early interpretation -- The Hodayot of the Maskil and the subjectivity of the masochistic sublime -- Conclusion.